25 Direct Admission to a Pacing Centre of Patients Who Present Urgently for Pacing: Retrospective Modelling Study of Feasibility, Potential Savings and Indicators of Suitability for Direct Transfer. (31st May 2014) - Dewhurst, Matthew; Di Marco, Luigi; McComb, Janet
Abstract : Introduction: Patients with symptoms consistent with bradycardia suggesting the need for permanent pacing who present to the emergency department in our city are admitted to a coronary care unit in one hospital and then transferred to a pacing centre in another. We investigated the potential for direct admission to our regional pacing centre and indicators of suitability. Methods: We undertook a retrospective observational study of patients who were referred urgently for pacing from one referring hospital to a pacing centre within the same city. Hospital records were reviewed for 138 consecutive patients over a 3 year period from April 2009–12 to determine indicators for suitability for direct admission to the pacing centre (based on symptoms, initial electrocardiogram and comorbidities). We also estimated potential hospital bed day savings, and in hospital complications that might have been avoided if the patient had been admitted directly to the pacing centre, and paced within 24 h. Results: 134/138 patients had sufficient data for analysis. The indication for pacing was AV block (AVB) in 60%, atrial fibrillation (AF) in 23%, sinus node disease (SND) in 16% and carotid hypersensitivity in 1. 87 patients had bradycardia <50 bpm on presentation; 75 (86%) were suitable for direct admission; 12 had co-morbidities, the majority either injury or infection, precluding early pacing, and the pacing indication was not immediately obvious in 3. 45 had a HR >50 bpm; 7 (16%) were suitable for direct admission, 5 had co-morbidity and in 33 diagnosis was not obvious. The heart rate at presentation was unknown in 6; 1 was suitable for direct admission, 1 had an infection and the diagnosis was not obvious in 4. Overall, 60% were considered suitable for direct admission from an emergency department to a pacing centre. Had these patients been admitted directly, 4.2 bed days per patient could have been saved, in addition to avoiding 4 temporary pacing wire placements and a bradycardia-related VT arrest. Predictors of suitability for direct transfer are shown in Tables 1 and 2 . The predictive ability of the clinical variables used according to multivariable linear regression analysis was 91.7%. Conclusions: The indication for pacing is obvious at presentation in the majority of patients who undergo non elective pacing. Triage to a pacing centre should be possible at presentation to an emergency department, using criteria including initial heart rate (≤50 bpm), high grade AVB and lack of co-morbidity, particularly infection or trauma, requiring urgent management in two thirds of patients.